2008
DOI: 10.1097/ana.0b013e318157a15a
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Events During Deep Brain Stimulation: The Experience at Cleveland Clinic

Abstract: This retrospective study demonstrates that age is an independent risk factor for complications during DBS procedures. Monitored anesthesia care using propofol seems to be a safe technique for DBS procedures; however, dexmedetomidine can also be used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 14 publications
1
73
0
2
Order By: Relevance
“…Only a few previous studies have reported the use of sedatives during DBS implantation surgery, [11][12][13] and none provided a systematic investigation of sedative effects produced on neuron discharge. A recent study of propofol effects on population activity in the STN suggested that the sedative appeared to interfere with microelectrode recording identification; however, single-unit recordings were not undertaken.…”
mentioning
confidence: 99%
“…Only a few previous studies have reported the use of sedatives during DBS implantation surgery, [11][12][13] and none provided a systematic investigation of sedative effects produced on neuron discharge. A recent study of propofol effects on population activity in the STN suggested that the sedative appeared to interfere with microelectrode recording identification; however, single-unit recordings were not undertaken.…”
mentioning
confidence: 99%
“…In general, DBS in the asleep-awake-asleep technique is well tolerated in most patients, but in some it remains a bad experience, and a few will suffer from posttraumatic stress disorder [12, 17, 25]. The feeling of being left alone or to be at someone’s mercy, reported by some patients, cannot be treated pharmacologically, but by therapeutic communication and relationship building.…”
Section: Discussionmentioning
confidence: 99%
“…While there have been a few reports of DBS surgeries that were occasionally performed without sedation by employing local anaesthesia with monitored care [8, 17], this is the first report of DBS without the principal need for sedation. And as the base for this achievement, for the first time a specific technique of communication and care is described in this article for a non-pharmacological dealing with the patient’s strain and stress during DBS, with major implications for communication during regional anaesthesia in general.…”
Section: Introductionmentioning
confidence: 99%
“…Specific diseaserelated considerations, such as PD and obesity, should be evaluated with respect to airway management. Intraoperative larynx related neuromuscular dysfunction has been described in PD patients, increasing the potential risk of aspiration [43].…”
Section: Local Anesthesiamentioning
confidence: 99%